Produtividade das culturas de soja e milho e alterações dos atributos quimicos do solo em função da aplicação do gesso agricola no Paraguai - Fois, Diego Augusto Fatecha (2018)
The cast is an agricultural source of Ca and S and brings improvements in chemical attributes, that acting produces a potential to increase yields of soybeans and maize. This work aimed to evaluate a productivity of soybean and corn crops and chemical soil attributes changes depending on the application of gypsum in Paraguai. The experiment took place in the district of Itakyry (Argissolo) and Minga Porá (Latossolo), Paraguai, using randomized blocks design with doses of gypsum (0, 100, 200, 400, 800 e 1600 kg ha‒1) and five repetitions a total of 30 parcels. In Minga Porá in June 2014 dolomitic limestone was applied at a dose of 2500 kg ha‒1. Gypsum was applied in september 2014 and evaluated two harvests of soybeans (2014/2015 and 2015/2016) two crops of corn crops second (2015 and 2016) and one soybean second (2015). In Minga Porá in september 2015 were reapplied gypsum doses, using factorial arrangement to subdivide parcels banded in blocks with two factors (doses and applications) and five repetitions a total of 60 parcels. For each crop and grain samples were collected in 2015/2016 foliar tissue samples were collected for determination of the levels of Ca, Mg, S, P and K. The soybeans were evaluated thousand grain mass, number of pods per plant, number of grains per plant, number of grains per pods and grain productivity. In maize, plant height, height of insertion of the spike, culm diameter, number of spikes, spike length, number of row of grains per spike, thousand grain and grain yield. Soil samples were collected in layers in 0‒10, 10‒20 e 20‒40 cm for analysis of pH CaCl2, pH SMP, Al+3, Al+H, availability of Ca, Mg, S, P e K, CTCpH7, bases saturation and Al+3. The components of productivity and levels of Ca, Mg, S, P, and K in soybeans and second corn were not influenced by gypsum, plus increased maximum of 4,71 g kg‒1 in the Ca content in grain until 750 kg ha‒1. The foliar contents of Ca, Mg, S, P, and K in soybeans have not increased. Maize leaf levels of Ca and S were increased and the concentration of Mg decreases. Critical levels of S, Ca, Mg and K available, bases saturation and Al saturation in the soil layer 0‒10, 10‒20 e 20‒40 cm do not correlate with the relative yields of soybeans and corn in the off-season and Argissolo and Latossolo. The application of gypsum not influence the pH, CaCl2 H+Al, availability of P and Al, bases saturation and Al saturation, the content of Ca increased linearly in the Argissolo 0‒10 cm layer, the Mg content decrease linearly in the Argissolo and from 1.000 kg ha‒1 in Latossolo, S levels increased linearly in three layers and there were 40 cm, K until mobility both in Latossolo and Argissolo.